Michelangelo's Christian Mysticism : Spirituality, Poetry and Art in Sixteenth-Century Italy / [electronic resource] - Prodan, Sarah Rolfe (Cambridge : Cambridge University Press, 2014)
In this book, Sarah Rolfe Prodan examines the spiritual poetry of Michelangelo in light of three contexts: the Catholic Reformation movement, Renaissance Augustinianism, and the tradition of Italian religious devotion. Prodan combines a literary, historical, and biographical approach to analyze the mystical constructs and conceits in Michelangelo's poems, thereby deepening our understanding of the artist's spiritual life in the context of Catholic Reform in the mid-sixteenth century. Prodan also demonstrates how Michelangelo's poetry is part of an Augustinian tradition that emphasizes mystical and moral evolution of the self. Examining such elements of early modern devotion as prayer, lauda singing, and the contemplation of religious images, Prodan provides a unique perspective on the subtleties of Michelangelo's approach to life and to art. Throughout, Prodan argues that Michelangelo's art can be more deeply understood when considered together with his poetry, which points to a spirituality that deeply informed all of his production.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Mysticism in literature